Analisis Faktor-Faktor yang Mempengaruhi Kecenderungan Penerimaan Opini Audit Going Concern - Arga Fajar Santosa; Linda Kusumaning Wedari (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2007)
This study provides the investigation over the acceptance of `going concern` audit opinion which can be performed by observing the company’s internal condition such as the audit quality, company’s financial condition, audit opinion prior year, company’s growth, and company size.Samples are obtained by sampling purposive method and obtained 310 observation data from 2001–2005. The logistic regression model testing is conducted four times because the financial condition variable has four different proxy models of bankcruptcy. The result of this research is that the audit quality and company growth do not influence on `going concern` opinion. The company size and company`s financial condition influences negatively toward the `going concern` opinion when the proxy model of bankcruptcy used the Altman Model and Springate Model, while the Zmijeski and the Revised Altman models are rejected. The `going concern` audit opinion prior year has positive influence toward `going concern` opinion.Keyword: Going concern opinion, audit quality, financial distress, audit opinion prior year, growth, company size, The Zmijeski (1984), The Altman Model (1968), Revised Altman model (1993), The Springate Model (1978)